One-step double reduction of aryl nitro and carbonyl groups using hydrazine - ROZAS, ISABEL; DIEZ CECILIA, ELENA; KELLY, BRENDAN (My University, 2011)
Single-step reduction of aryl nitro and carbonyl groups to the corresponding synthetically useful alkyl-anilines occurs with excellent yields by treatment with hydrazine and a base in a solvent-free reaction. The method has been applied to a broad range of compounds with different properties. Investigations into the mechanism of the reduction reveal that each group is reduced independently. A mechanism is proposed for this novel reduction of aromatic nitro groups.
PUBLISHED
Keywords: Physical chemistry; carbonyl; aryl nitro